Effect of hybrid working on employee engagement - Siddika, Bilkis Afroza (Goodwood Publishing, 2025)
Purpose: During the COVID-19 pandemic, partial homeworking or hybrid working gained popularity among employees and employers across the world. Since then, many organisations continue to implement hybrid working as a high performing work practice (HPWP) to improve employee performance. This study explores the effects of hybrid working on employee work engagement on the scale of the level of energy, work involvement, concentration, and enthusiasm. This study also investigated the factors that influence employee engagement in hybrid work. Research methodology: Using a cross-sectional study design with snowballing sampling technique, interview data of twenty nine IT employees were collected. Interview data were analysed thematically using NVivo software. Results: The qualitative analysis of interview data reveals that despite some factors of homeworking that affect work engagement negatively, hybrid working has potentials to improve work engagement through increasing their work and family life balance and reducing commuting exhaustion. Conclusions: Hybrid working can enhance employee engagement by reducing commuting stress and supporting better work-life balance, particularly in terms of energy and flexibility. However, challenges such as communication barriers and work-family conflicts especially among female employees may hinder its effectiveness. With adequate organizational support and clear structure, hybrid working can serve as a strategic approach to boosting employee engagement. Limitations: Qualitative analysis of only twenty six sample of only one organization is not sufficient for generalizing. A quantitative analysis using data of broader sample may provide a result generalizable to other types of organizations or regions. Contribution: This study contributes to the understanding of factors that influence employee work engagement by emphasizing the benefits of hybrid working to improve employee engagement, an important facilitator of higher performance. Novelty: This research made a comparison between homeworking, onsite working and hybrid working, and explored the factors of different work arrangement that influence employee engagement, an area that has not received enough attention in the existing literature.